The Influence of Role Playing Models on Students' Concept Understanding and Communication Skills in Social Studies Learning in Elementary Schools - Nur Rohmah; Nurmalina; Kasman Ediputra (Institute of Educational, Research, and Community Service, 2024)
This research aims to analyze the influence of the role-playing model on the conceptual understanding and communication skills of students in Social Studies learning at elementary school. The role-playing model was chosen as a teaching strategy believed to enhance student engagement, learning motivation, and conceptual understanding through a more interactive and contextual approach. The research method used is quantitative with a quasi-experimental design. The subjects of this research were fifth-grade students at SDN 2 Tanjungsamak and SDN 1 Tanjungsamak. Data collection was carried out through tests of conceptual understanding and communication skills. The results of the study showed that the use of the role-playing model significantly improved students' conceptual understanding and communication skills in Social Studies learning. Students involved in the role-playing model demonstrated better understanding of the taught material and were able to communicate their ideas more effectively. This research makes a significant contribution to the field of education, particularly in developing effective teaching methods in elementary schools. Therefore, it is hoped that teachers can implement the role-playing model as an alternative teaching strategy to enhance the quality of Social Studies learning.